Circular economy and the policy: A framework for improving the corporate environmental management in supply chains. (15th October 2020) - Kazancoglu, Ipek; Sagnak, Muhittin; Kumar Mangla, Sachin; Kazancoglu, Yigit
Abstract: The transition to the circular economy (CE) creates value through the closed‐loop systems, reverse logistics, product life cycle management, and clean production in terms of corporate environmental management. During this transition process, the organization faces many barriers such as financial, organizational, technology‐based, social, policy‐related, market‐based, and logistics‐based barriers. The objectives of this study are to propose a framework highlighting policy‐related barriers for a supply chain in the transition to CE and finally discuss potential implications on enhancing corporate environmental performance of a business. Further, this study evaluates the causal relationships between the policy‐related barriers using fuzzy Decision‐Making Trial and Evaluation Laboratory (DEMATEL) method. The application was conducted in an apparel firm in Turkey. From findings, lack of legislation for efficient CE (C4), lack of mandatory requirements and responsibilities for manufacturers/suppliers for the CE (C17), and lack of government support for environmentally friendly policies (C2) are revealed as the most important barriers, respectively. It is found that lack of attitude and awareness about CE in government institutions (C19) is the most influencing factor, whereas lack of effective recycling policies to achieve quality in waste management (C8) is the most influenced factor. The recommendations were developed for enhancing the corporate environmental performance of businesses through incentives and unique rewards, improving communication among stakeholders, the government's perception of CE and current linear economy, cooperation with nongovernmental organization (NGOs) and civil actions, the vision of government towards circular principles, the circular public procurement, the local governments in circular policymaking, and awareness of bureaucracy and government officials.